Ministering in patronage cultures : biblical models and missional implications - Georges, Jayson (Downers Grove.: : IVP Academic, 2019)
"Patronage is a central part of global cultures and the biblical story of God's mission, yet many Westerners misunderstand or ignore this concept. In this resource for ministry practitioners and lay Christians alike, Jayson Georges brings his crosscultural experience and biblical insights to bear on the topic of patronage, with sections on cultural issues, biblical models, theological concepts, and missional implications"--
The Problems of Patronage -- CULTURAL ISSUES -- The Meaning of Patronage -- Expressions of Patronage -- Misperceptions of Patronage -- BIBLICAL MODELS -- Yahweh and Israel -- Jesus and the Kingdom -- Paul and the Church -- THEOLOGICAL TRUTHS -- God as Patron -- Sin as Ingratitude -- Salvation as Patronage -- MISSIONAL IMPLICATIONS -- Engaging Patronage -- Transforming Relationships -- Reframing the Christian Life.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed
Keywords: Christianity and culture; Interpersonal relations -- Religious aspects -- Christianity; Missions